(untitled) (CIPEEX, 2023)
Social media has become popular in recent decades as one of the main forms of communication, bringing people together through virtual environments where they share knowledge and experiences. However, their misuse, whether due to excessive exposure or frequenting hostile environments, can lead to symptoms involving anxiety and depression in children, adolescents, and young adults. The objective of this work was to analyze the influence of social media use by children, adolescents, and young adults in relation to anxiety and depression. The methodology used was a systematic literature review of studies. It was observed that social networks have an impact on a considerable portion of their users, who may exhibit symptoms of anxiety and depression; however, it is important that more studies are conducted to better understand this phenomenon.